Evaluation of oral health of 6 to 10-year-old asthmatic children receiving bronchodilator through inhaler - Sudhir Kumar; Namita Kalra; Rishi Tyagi; M M A Faridi; Amit Khatri; V N V Satish (Wolters Kluwer Medknow Publications, 2019)
Aim: The aim of this study was to evaluate the oral health status in 6 to 10-year-old asthmatic children receiving bronchodilator (salbutamol, salmeterol, etc.) through inhaler and compare them with nonasthmatic healthy children. Settings and Design: The present study was carried out at pediatric and pedodontic department and neighboring government school. It was an observational and case-control study. Statistical Analysis: All data were analyzed using SPSS 20.0 software program and presented as mean ± standard error of mean. Chi-square test was used for the categorical data between groups. Numerical data were analyzed by Mann-Whitney U-test and t-test. Kruskal-Wallis test was performed for comparisons of median value of decayed, missing, filled surface and Decayed, Missing, Filled Surface (dmfs and DMFS) for different variables within asthmatic group. Mann-Whitney U-test for multiple comparisons and P value was adjusted according to Bonferroni correction. Negative binomial analysis was used to calculate adjusted dmfs and DMFS, and univariate analysis of variance was used for adjusted mean plaque and gingival index. Materials and Methods: The study group composed of 70 asthmatic and 70 nonasthmatic children with the same age and social background aged between 6 and 10 years old. Oral health status was assessed using caries, plaque, and gingival index. Dental caries examination was done using the WHO criteria (1997), plaque index by Silness and Loe in 1964 and gingival health by Loe and Silness in 1963. Results: The children in the asthmatic group had significantly higher caries prevalence, severity of dental plaque, and gingivitis compared with the nonasthmatic group. Plaque accumulation and gingivitis increased significantly as severity and duration of asthma increased. Conclusions: Bronchial asthma had an overall deleterious effect on caries prevalence and severity, plaque, and gingivitis on primary and permanent teeth.